Concentrations of minerals in the canine prostatic fluid. Issue 8 (25th June 2019) - Umbach, Anne‐Kathrin; Failing, Klaus; Goericke‐Pesch, Sandra; Wehrend, Axel
Abstract: Current knowledge about the composition of the prostate fluid in healthy male dogs is limited and restricted to small case numbers. Furthermore, published data often vary significantly regarding sample processing and analytical methods. Therefore, we aimed to provide data on the composition of electrolytes and minerals in the canine prostatic fluid in a larger population ( n  = 30 dogs/samples) and to compare these results with the existing literature. Concentrations of sodium, potassium and copper analysed in our population were most consistent with those in the literature. Different to this, concentrations of total calcium, magnesium, zinc and inorganic phosphate varied. Whereas magnesium, zinc and inorganic phosphate seemed to depend on the analysis method, total calcium concentrations differed if centrifugation was performed or not. Our results clearly indicate a need for standardization of methods for analysis of seminal plasma components.